446. COVID 19 Pandemicity: a global situation report as of June 9, 2020. (31st December 2020) - Sanyaolu, Adekunlle; Okorie, Chuku; Hosein, Zaheeda; Patidar, Risha; Desai, Priyank; Prakash, Stephanie; Jaferi, Urooj; Mangat, Jasmine; Marinkovic, Aleksandra
Abstract: Background: The World Health Organization (WHO) declared severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) a pandemic on March 11, 2020. This report takes a closer look at the cases, fatalities, and recoveries in different regions of the world with details regarding the geographic scale of SARS-CoV-2 spread, risks, and the subsequent impact on the countries affected. Also, this report discusses some effective measures that were carried out by some countries that helped them to mitigate the pandemic and flatten the curve of COVID-19 spread as early as possible. Methods: Our research was conducted via an electronic literature review on PubMed, Google Scholar, and MedLine Plus. Data were then collected from peer-reviewed articles that included applicable keywords and published between January 1, 2020, and June 9, 2020 Results: The rapid spread of infection has impacted over 200 countries and territories to date. As of June 9, 2020, there were 7, 039, 918 confirmed cases and 404, 396 deaths globally. The USA is the North American country with the highest number of confirmed COVID 19 cases with 1, 993, 560. In South America, total confirmed cases in Brazil are 691, 758. The most affected country in the African region is South Africa with 50, 879. In Europe, the Russian Federation top with 485, 253 confirmed cases. China with 84, 638 is still the Western Pacific country with the most confirmed COVID 19 cases. India had 266, 598 total confirmed cases and Australia reported 7, 265 confirmed cases. Fatalities recorded similar patterns regionally except in Europe where the UK recorded the highest number of fatalities with 40, 597 deaths and Iran had the highest number of fatalities with 5, 957 cases in Asia. The goal of the practice "slowing the spread" is to prevent hospital systems from being strained beyond their capacity, thus resulting in less mortality. Countries yet to see the peak would benefit substantially by implementing aggressive social distancing, self-isolation, closure of schools and other institutions, encouraging working from home, and/or placing hard limits on the size of crowds at events. Confirmed cases of COVID-19 globally, as of June 9, 2020. Confirmed fatalities due to COVID-19 globally, as of June 9, 2020. Conclusion: As the number of cases increases, an immediate need to "flatten the curve" is essential to avoid catastrophic overwhelming of hospital systems across the affected countries. Disclosures: All Authors : No reported disclosures